2023
DOI: 10.1002/ece3.10353
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of a hydropower project on a high‐value Asian elephant population

Kris Budd,
Daophone Suddychan,
Martin Tyson
et al.

Abstract: Habitat loss and fragmentation are leading contributors to the endangered status of species. In 2006, the Nakai Plateau contained the largest known Asian elephant (Elephas maximus) population in the Lao People's Democratic Republic (Lao PDR), and the population was among those with the highest genetic diversity reported for Asian elephants. In 2008, completion of the Nam Theun 2 hydroelectric dam inundated much of the Plateau, resulting in the loss of 40% of elephant habitat. We studied elephant presence, move… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
(90 reference statements)
0
0
0
Order By: Relevance
“…The conservation of Sumatran elephants is increasingly threatened when they are outside the conservation area. Several studies mentioned that the highest level of conflict between elephants and humans is found in spaces that were shared by humans and elephants (Sitompul et al 2013b;de Mel et al 2022;Rahman et al 2022;Budd et al 2023). Currently, 85% of the Sumatran elephants' habitat is outside the conservation area (Gopala et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The conservation of Sumatran elephants is increasingly threatened when they are outside the conservation area. Several studies mentioned that the highest level of conflict between elephants and humans is found in spaces that were shared by humans and elephants (Sitompul et al 2013b;de Mel et al 2022;Rahman et al 2022;Budd et al 2023). Currently, 85% of the Sumatran elephants' habitat is outside the conservation area (Gopala et al 2011).…”
Section: Introductionmentioning
confidence: 99%